Board of Commissioners Educational Background And Sustainability Report Quality - Tanputra, Sebastian; Harymawan, Iman; Nasih, Mohammad (Jurnal Dinamika Akuntansi, 2023)
Purpose: This research is aims to determine the relationship between the educational background of the board of commissioners on the quality of the sustainability report in companies listed on the Indonesia Stock Exchange.Method: Sources of research data consist of the annual reports, sustainability reports, global reporting websites (GRI), and Quacquarelli Symonds (QS) World University Ranking. The sampling method used was side purposive, in order to obtain as many as companies that had met the criteria to be used as research samples for 5 (five) years, 2015-2019 which is 258 companies. This study uses a multiple regression model with a cluster by the firm from STATA 14 software to determine the direction and magnitude of the influence of independent variables on the dependent variable.Findings: This study found that the BOC educational background with undergraduate degree from reputable university showed a positive and significant relationship towards sustainability report quality. In contrast, educational background defined by level of education indicates insignificant effect towards sustainability report.Novelty: the role of BOC in Indonesia is to supervise the quality of the company's report, therefore those results indicate that top-level universities have a role to form character and concern for environmental problems.